Perioperative Management of Patients Treated with Angiotensin-Converting Enzyme Inhibitors and Angiotensin II Receptor Blockers: A Quality Improvement Audit. Issue 3 (May 2016) - Vijay, A.; Grover, A.; Coulson, T. G.; Myles, P. S.
Previous studies have shown that patients continuing angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers on the day of surgery are more likely to have significant intraoperative hypotension, higher rates of postoperative acute kidney injury and lower incidences of postoperative atrial fibrillation. However, many of these studies were prone to bias and confounding, and questions remain over the validity of these outcomes. This observational, before-and-after quality mprovement audit aimed to assess the effect of withholding these medications on the morning of surgery. We recruited 323 participants, with 83 (26%) having their preoperative angiotensin-converting enzyme inhibitor (ACEi) or angiotensin II receptor blocker (ARB) withheld on the day of surgery. There were only very small Spearman rank-order correlations between time since last dose of these medications (rho −0.12, P =0.057) and intraoperative and recovery room intravenous fluid administration (rho −0.11, P =0.042). There was no statistically significant difference between the continued or withheld groups in vasopressor (metaraminol use 3.5 [1.5–8.3] mg versus 3.5 [1.5–8.5] mg, P =0.67) or intravenous fluid administration (1000 ml [800–1500] ml versus 1000 [800–1500] ml, P =0.096), nor rates of postoperative acute kidney injury (13% vs 18%, P =0.25) or atrial fibrillation (15% versus 18%, P =0.71). This audit found no significant differences in measured outcomes between the continued or withheld ACEi/ARB groups. This finding should be interpreted with caution due to the possibility of confounding and an insufficient sample size. However, as the finding is in contrast to many previous studies, future prospective randomised clinical trials are required to answer this important question.